Safety and immunogenicity of inactive vaccines as booster doses for COVID-19 in Türkiye: A randomized trial - Ahmet Omma; Ayse Batirel; Mehtap Aydin; Fatma Yilmaz Karadag; Abdulsamet Erden; Orhan Kucuksahin; Berkan Armagan; Serdar Can Güven; Ozlem Karakas; Selim Gokdemir; Lutfiye Nilsun Altunal; Aslihan Ayse Buber; et al. (Taylor & Francis Group, 2022)
Protective neutralizing antibody titers reduce in time after COVID-19 vaccinations, as in individuals who have had COVID-19. This study aimed to evaluate the safety and immunogenicity of CoronaVac and TURKOVAC vaccines used as a booster dose after CoronaVac primary vaccination. This double-blind, randomized, controlled, phase II, multicenter study included healthy male and female adults (18-60 years) who were vaccinated with two doses of CoronaVac vaccine and did not exceed the duration of at least 90 days and a maximum of 270 days from the second dose of vaccination. Among 236 eligible volunteers, 222 were recruited for randomization between July 12, 2021 and September 10, 2021; 108 and 114 were randomized to the TURKOVAC and CoronaVac arms, respectively. The primary endpoint was adverse events (AEs) (ClinicalTrials.gov; Identifier: NCT04979949). On day 28, at the neutralizing antibody threshold of 1/6, the positivity rate reached 100% from 46.2% to 98.2% from 52.6% in the TURKOVAC and CoronaVac arms, respectively, against the Wuhan variant and the positivity rate reached 80.6% from 8.7% in the TURKOVAC arm vs. 71.9% from 14.0% in the CoronaVac arm against the Delta variant. IgG spike antibody positivity rate increased from 57.3% to 98.1% and from 57.9% to 97.4% in the TURKOVAC and CoronaVac arms, respectively. The TURKOVAC and CoronaVac arms were comparable regarding the frequency of overall AEs. Both vaccines administered as booster yielded higher antibody titers with acceptable safety profiles.